The Relevance of Pragmalinguistic Failure to Language Teaching - Juraidi, Agus (LPPM Universitas Bumigora Mataram, 2018)
Pragmatic competence refers to the capacity to use a language effectively in order to fulfill a certain goal and to understand language in context. When people are unable to understand what is meant by what is said, the result is communication will breakdown, and so called pragmatic failure. Some factors cause pragmatic failure; firstly, failure to express or interpret speaker-meaning in which communication breaks down if either level of meanings (sense and reference) or (force or value) is not successfully produced or interpreted. Secondly, failure to observe cultural values in which social conditions on language in use are different and utterer or the interpreter fails to observe the cultural values. Thirdly, culture-specific pragmatic features; mental sets: a frame of mind involving an existing disposition to think of a problem or a situation in a particular way. The implications of pragmalinguistic failure to teaching second and foreign language teaching are that first, learners need to understand why such conventions are accepted. Second, language learners need to understand what native speakers mean when they use the language. Third, teacher is expanding students' knowledge and understanding of L2 pragmatic features regarding positive/negative pragmatic transfer from their first language (L1). Next, adult learners rely heavily on universal or L1 based pragmatic knowledge. Finally, teachers must be sufficiently socialized to L2 pragmatic practices, so that they can comfortably draw on those practices as part of their communicative and cultural repertoire.